METHOD FOR OPTIMIZING THE TREATMENT OF ACUTE RESPIRATORY DISEASES IN CHILDREN - Нікітіна, Надія; Беспалова, Алла; Кукушкин, Віталій (SWorldJournal, 2024)
The results of treatment of children with acute respiratory tract diseases using the medicament Bon-appetit during a period of decreased activity of the inflammatory process are presented. The medicament is well tolerated (85%) with minor side effects (14